2016
DOI: 10.1038/npp.2016.82
|View full text |Cite
|
Sign up to set email alerts
|

LSD Acutely Impairs Fear Recognition and Enhances Emotional Empathy and Sociality

Abstract: Lysergic acid diethylamide (LSD) is used recreationally and has been evaluated as an adjunct to psychotherapy to treat anxiety in patients with life-threatening illness. LSD is well-known to induce perceptual alterations, but unknown is whether LSD alters emotional processing in ways that can support psychotherapy. We investigated the acute effects of LSD on emotional processing using the Face Emotion Recognition Task (FERT) and Multifaceted Empathy Test (MET). The effects of LSD on social behavior were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
196
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(230 citation statements)
references
References 37 publications
26
196
6
2
Order By: Relevance
“…Specifically, MDMA mainly induces the transporter-mediated release of serotonin (Hysek et al 2012) and stimulates oxytocin secretion Ramos et al 2013), which has been implicated in the prosocial effects of MDMA (Ramos et al 2013). Additionally, the serotonin receptor agonist LSD (Rickli et al 2016) stimulated oxytocin secretion (Schmid et al 2015a), produced prosocial effects, and enhanced emotional empathy in the MET (Dolder et al 2016). In contrast to MDMA and LSD and our prediction, the present study found that alcohol did not change oxytocin levels in 30 female and 30 male participants at a low dose (0.27 g/kg) as similarly shown for a high dose of alcohol (0.8 g/kg) in seven male subjects (Bershad et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, MDMA mainly induces the transporter-mediated release of serotonin (Hysek et al 2012) and stimulates oxytocin secretion Ramos et al 2013), which has been implicated in the prosocial effects of MDMA (Ramos et al 2013). Additionally, the serotonin receptor agonist LSD (Rickli et al 2016) stimulated oxytocin secretion (Schmid et al 2015a), produced prosocial effects, and enhanced emotional empathy in the MET (Dolder et al 2016). In contrast to MDMA and LSD and our prediction, the present study found that alcohol did not change oxytocin levels in 30 female and 30 male participants at a low dose (0.27 g/kg) as similarly shown for a high dose of alcohol (0.8 g/kg) in seven male subjects (Bershad et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The three aspects of empathy were each tested with 20 stimuli with positive valence and 20 stimuli with negative valence. Explicit emotional empathy was the primary predefined outcome measure because it is most robustly altered in acute pharmacological challenge studies (Dolder et al 2016;Hurlemann et al 2010;Hysek et al 2014;Schmid et al 2014).…”
Section: Multifaceted Empathy Testmentioning
confidence: 99%
“…[1,[4][5][6] Additionally, LSD has been shown to acutely alter emotion processing in ways that may be useful for LSD-assisted psychotherapy. [6] However, under uncontrolled conditions, adverse psychological reactions including panic are common effects of LSD use. [7,8] LSD consists of an ergoline skeleton in which the (5R,8R)-configuration confers psychoactive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research with LSD, psilocybin, and other phenethylamine derivatives is currently undergoing a major revival, and current studies are exploring the potential role of hallucinogens in the treatment of alcohol dependence [158] as well as mood disorders [159] and anxiety [160]. In particular, a recent study carried out by Dolder et al has demonstrated that the administration of 100 µg of LSD enhances emotional empathy in healthy volunteers [161] However, more research needs to be performed on the differential effects of LSD and other hallucinogenic drugs at low and high doses: while at lower doses they activate 5-HT system, likely producing therapeutic effects for depression, drug dependence [159], and anxiety [160], it is clear that at high doses they activate the dopaminergic system, producing psychosis and similar effects [115]. …”
Section: Resultsmentioning
confidence: 99%